THE IMPORTANCE OF STUDENT’S SOCIOCULTURAL COMPETENCE DURING THEIR FOREIGN LANGUAGE STUDIES - Matanat Mirfayaz Mammadova (International Journal of Innovative Technologies in Social Science, 2023)
The article analyzes the social component of the updated speech portrait of a university specialist. The sociocultural dominant of intercultural speech interaction is determined by the position of the individual in the social system, the situation of communication, his profession, region of origin, and age. In this regard, the subjects of communication are faced with various features of communication: this is communicative behavior, the cultural space of communication, the linguistic personality of a foreign language with an individually formed picture of the world. English language instruction at the Language Pedagogical Institute is governed by educational standards that call for a move to higher level of foreign language skill as measured by the mainstream European scale of non-native language proficiency. When learning a foreign language, particular focus should be placed on the practical aspects of mastering the language while taking into account contemporary linguistic trends, motivating factors, and the psychology-pedagogical aspects of oral speaking. Learning a foreign language becomes a creative process that opens up the culture and mindset of the nation where it is being learned. If a sociocultural aspect of learning foreign language content is fully realized, this will encourage students' interest in the subject and lead to more fully realized language mastery. The sociocultural field of research concerned with instructing the interpretation of foreign language speech is taken into consideration at the junction of competency-based and intercultural approaches. Emphasis is placed on the value of learning how to identify and evaluate the significance of social elements' influences on a speaker's speech behavior.